Modeliranje nefunkcijskih svojstava programskih komponenata signalizacijskih protokola: doktorski rad - Hribar, Lovre; Lovrek, Ignac; Huljenić, Darko (Zagreb: L. Hribar ; Fakultet elektrotehnike i računarstva, 2015)
Komponentni pristup razvoju programskog proizvoda jedan je od načina razvoja programskog proizvoda koji omogućuje programskim inženjerima razvoj složenih sustava. Istraživanje programskih komponenti signalizacijskih protokola, provedeno u ovom doktorskom radu, motivirano je analizom nefunkcijskih obilježja i njihovim doprinosima u poboljšanju kvalitete programskih komponenti. Analiza se temelji na primjeni najboljih praksi u programskom inženjerstvu zasnovanom na programskim komponentama. Odabrana je karakterizacija nefunkcijskih svojstava prema Sommervilleu jer je primjerena evoluciji i ponovnoj uporabi programskih komponenti signalizacijskog protokola. Analizom nefunkcijskih obilježja komponentnog sustava za signalizacijske protokole u čvorovima telekomunikacijske mreže, u ovom doktorskom radu osmišljen je i istražen model evolucije programskih komponenti signalizacijskih protokola. Model se temelji na razvoju pojedine programske komponente kroz životni ciklus i temeljem dobivenih parametara analize (prvenstveno praćenjem pojavnosti neispravnosti) model osigurava veću kvalitetu evolucije programske komponente za daljnje životne cikluse. Temeljem definiranih parametara postojećeg procesa razvoja programskog proizvoda predloženo je unaprjeđenje razvoja pojedine programske komponente signalizacijskog protokola. Analiza nefunkcijskih obilježja i utjecaj na kvalitetu programskog proizvoda provela se na telekomunikacijskom čvoru u nepokretnoj mreži korištenjem različitih matematičkih modela. Doktorski rad temelji se na empirijskim istraživanjima signalizacijskih protokola u čvorovima nepokretne telekomunikacijske mreže.
Ključne riječi:
– programska komponenta
– programsko inženjerstvo zasnovano na komponentama
– telekomunikacijska mreža
– signalizacijski protokol
– nefunkcijsko obilježje
– evolucija programske komponente
– ponovna iskoristivost programske komponente
– kvaliteta programskog proizvoda
This thesis is the result of research procedures for the signalling protocols design and software implementation in the network systems. Signalling protocols are called communication protocols that provide call control and services in the network. These protocols are well-defined and specified from the functional point of view, so that the component approach to program design allows achieving the required quality, at acceptable costs of development and maintenance, and what specifically affects ability to re-use software protocol components. In that direction, reserch of nonfunctional properties for software components of signalling protocols are conducted and discusses.
The first, introductory chapter summarizes the scope and content of the doctoral research dissertation.
The second chapter describes the motivation and research objectives, along with debate the state of related works and set theese three hypothesis:

Hypothesis 1: Defining the component model for the telecommunications system which is not originally componently designed contributes to the quality of software products;

Hypothesis 2: Defined and measurable non- functional parameters facilitate the re-use and the application of signalling software components for which functional parameters are specified and standardized;

Hypothesis 3: Application of the component models and measurable non-function parameters contribute to the improvement of the software products development process.

In the third chapter, "Component Based Software Development", after defining the components and the general concept of the component development, the structure of processes, functionality and components capabilities and their quality is processed.
Non-functional properties of the software components are the subject of the fourth chapter. In order to identify such properties relevant to signalling protocols, an analysis of different approaches to the classification of non-function requirements has been done. Results of the studies conducted by Boehm, McCall, Grady, Dromey, Sommerville, Glinz, Van Lamsweerde and approach contained into ISO 9126 standard (Software Engineering Product Quality Part 1: Quality model) are isolated and compared.
In the fifth chapter, "Signalling Protocol Component Model", starting point was a double-layers model template of the working group Next Steps in Signaling (NSIS) within the IETF (Internet Engineering Task Force) and on top of that a third layer was introduced, the adaptation layer, between the transport and signalling (application) layers in order to cover all aspects of the performance of signalling protocols in telecommunication network nodes. Two groups of functional requirements are defined which are related to the product and software development process and non-functional properties of software components are associated: the number of interfaces between components, received and sent information elements set, component size, amount of available registers, primary testing coverage and the amount of reported faults. Re-usability of signaling protocol software components is processed from the life cycle perspective of a defined process elements and process operations.
"The Evolution of Signalling Protocols Software Components" (chapter 6) is specified by the machine model M = ?S, U, ?, q0, F?, where S is a finite set of states in the evolution of software components, U is the accepted final set of input trigger in the evolution of software components, ? is the transition function defined by S x S › U, S0 is the initial state of program components (prior to any input trigger), S0 ? S, or S0 ? F if the initial state must be acceptable state, F is a subset of S, F ? S and F is a set of acceptable states in the evolution of software components. The model consists of 6 process steps, each with one or more processing elements which comprises the determination of functional and nonfunctional requirements of a new component and the selection of the most suitable software components for the evolution from existing component repositories based on the principle of re-usability.
Similarity criteria have been proposed that underpin the components selection, which is conducted on the basis of determining the classification of the k-nearest neighbors. Special attention is directed to the non-functional properties that describes the reported software faults (Weibull distribution parameters ß and ?) and the process of registration, collection, processing and correction of software faults.
In the seventh chapter, "The Empirical Verification of the Model", the proposed procedure of nonfunctional properties modelling has been analyzed in six case studies for signalling protocol SIP (Session Initiation Protocol) and protocol BICC (Bearer Independent Call Control) within the AXE technology switching nodes. The data were analyzed in detail. The proposed hypotheses are confirmed.
In conclusion chapter, the research results are summarized and the possible directions of future research are indicated.
Keywords:
– software component
– component based software engineering
– telecommunication network
– signalling protocols
– non-functional properties
– software component evolution
– software component re-usability
– software component quality
Bibliografija str. 157-162.